(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2025)
Abstract Folklore plays a vital role in Malay traditional culture, emphasizing elements of Malay identity that have been creatively transformed into 3D animated films. This study examines the characters adapted from these folklores, focusing on their symbolism and the traditional elements incorporated into their costumes. However, existing documentation on costume design often neglects the adaptation process and its relationship to the character, theme, and culture as visual metaphors. The objective of this study is to develop the Character Costume Symbolism Relevance Framework (CCSRF), specifically focusing on the costume designs of folklore characters in the 3D animated film “Upin and Ipin: Keris Siamang Tunggal.". A qualitative approach involving interviews, observations, and literature reviews was employed. Peirce’s Triadic Semiotic Theory was utilized to identify the key components representing the representation, object, and interpretation. The findings indicate that character identity, external factors, and visual elements are three interconnected components that influence costume design. These components work together to express the character’s identity through the interpretation of relevant symbols in the design. In conclusion, this study demonstrates that the development of this framework can enhance the creativity of artists in producing high-quality Malaysian animated costume designs. Abstrak Cerita rakyat merupakan sebahagian daripada budaya tradisional masyarakat Melayu yang mempunyai representasi unsur-unsur Melayu yang diolah dalam bentuk filem animasi 3D. Adaptasi karakter daripada cerita rakyat dilihat daripada sudut semiotik terhadap rekaan kostum yang berkonsepkan elemen tradisional. Namun begitu, dokumentasi terhadap rekaan kostum sedia ada dilihat kurang memberi focus terhadap proses pengolahan dan relevansi kepada karakter, tema, dan budaya sebagai suatu metafora visual. Kajian ini bertujuan membangunkan Kerangka Relevansi Simbolisme Kostum Karakter (KRSKK) berdasarkan rekaan kostum karakter cerita rakyat dalam filem animasi 3D Upin and Ipin Keris Siamang Tunggal. Kajian ini menggunakan pendekatan kualitatif, iaitu temu bual separa berstruktur, pemerhatian dan kajian literatur. Teori Semiotic Triadic oleh Peirce diadaptasi untuk mengenal pasti komponen- komponen utama yang mewakili representasi, objek, dan interpretasi. Hasil dapatan kajian secara keseluruhan mendapati identiti karakter, faktor luaran dan elemen visual merupakan tiga komponen yang saling berinteraksi membentuk suatu rekaan kostum. Ketiga-tiga komponen utama ini membentuk interaksi secara kolektif yang melambangkan identiti karakter melalui relevansi tafsiran simbol terhadap rekaan kostum. Kesimpulan daripada kajian ini menunjukkan penghasilan kerangka ini mampu melonjakkan kreativiti pengkarya dalam menghasilkan rekaan kostum animasi Malaysia yang lebih berkualiti.